MUTASI, PROMOSI JABATAN DAN PRESTASI KERJA PEGAWAI - Febri Yuliani, Fitri Apriliana, Harapan Tua, (Jurnal Ilmu Administrasi Negara, 2019)
Movements, Job Promotions and Employee Work Achievements. The purpose of this study was to determine the effect of mutations and promotion on the work performance of employees at the Regional Personnel Agency of Riau Province. This type of research is quantitative. The study population was all of the State Civil Apparatus of the Riau Province Regional Personnel Agency as many as 63 people (census research). Data collection techniques are questionnaires, observation and documentation. Data analysis is multiple linear regression. The results of the study showed that the variable mutation and job promotion had a significant effect on the work performance of employees at the Regional Personnel Agency of Riau Province. This shows that if the Riau Province Regional Personnel Agency wants to improve the work performance of its employees, the approach to mutation and promotion will be achieved. Simultaneously mutations and job promotions affect the work performance of employees at the Riau Province Regional Personnel Agency, with a significant degree of influence. Where from the R2 determination test it is known that simultaneously the mutation variables and promotion have an influence of 60.8% and the remaining 39.2% is influenced by variables not examined in this study such as leadership, organizational climate and motivation.